Identification of Potential Calorie Restriction-Mimicking Yeast Mutants with Increased Mitochondrial Respiratory Chain and Nitric Oxide Levels - Bin Li; Craig Skinner; Pablo R. Castello; Michiko Kato; Erin Easlon; Li Xie; Tianlin Li; Shu-Ping Lu; Chen Wang; Felicia Tsang; Robert O. Poyton; Su-Ju Lin (Journal of Aging Research)
Calorie restriction (CR) induces a metabolic shift towards mitochondrial respiration; however, molecular mechanisms underlying CR remain unclear. Recent studies suggest that CR-induced mitochondrial activity is associated with nitric oxide (NO) production. To understand the role of mitochondria in CR, we identify and study Saccharomyces cerevisiae mutants with increased NO levels as potential CR mimics. Analysis of the top 17 mutants demonstrates a correlation between increased NO, mitochondrial respiration, and longevity. Interestingly, treating yeast with NO donors such as GSNO (S-nitrosoglutathione) is sufficient to partially mimic CR to extend lifespan. CR-increased NO is largely dependent on mitochondrial electron transport and cytochrome c oxidase (COX). Although COX normally produces NO under hypoxic conditions, CR-treated yeast cells are able to produce NO under normoxic conditions. Our results suggest that CR may derepress some hypoxic genes for mitochondrial proteins that function to promote the production of NO and the extension of lifespan.